2004
DOI: 10.1105/tpc.017749
|View full text |Cite
|
Sign up to set email alerts
|

Electron Tomographic Analysis of Somatic Cell Plate Formation in Meristematic Cells of Arabidopsis Preserved by High-Pressure Freezing[W]

Abstract: We have investigated the process of somatic-type cytokinesis in Arabidopsis (Arabidopsis thaliana) meristem cells with a three-dimensional resolution of~7 nm by electron tomography of high-pressure frozen/freeze-substituted samples. Our data demonstrate that this process can be divided into four phases: phragmoplast initials, solid phragmoplast, transitional phragmoplast, and ring-shaped phragmoplast. Phragmoplast initials arise from clusters of polar microtubules (MTs) during late anaphase. At their equatoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
331
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(347 citation statements)
references
References 71 publications
14
331
1
1
Order By: Relevance
“…Preliminary results from our laboratory and Martin Hülskamp's group suggest that putative components of the ESCRT machinery are necessary for the proper execution of cytokinesis in Arabidopsis (V. Winter et al, unpublished; C. Spitzer et al, unpublished). This putative ESCRT function is corroborated by recent findings that MVBs are enriched at the newly formed cell plate during cytokinesis [15,16]. The identification of mutants that affect components of the ESCRT-machinery, of suitable markers for the characterization of MVB maturation, and of their endogenous cargos should shed light on the cellular processes that MVB are involved with.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Preliminary results from our laboratory and Martin Hülskamp's group suggest that putative components of the ESCRT machinery are necessary for the proper execution of cytokinesis in Arabidopsis (V. Winter et al, unpublished; C. Spitzer et al, unpublished). This putative ESCRT function is corroborated by recent findings that MVBs are enriched at the newly formed cell plate during cytokinesis [15,16]. The identification of mutants that affect components of the ESCRT-machinery, of suitable markers for the characterization of MVB maturation, and of their endogenous cargos should shed light on the cellular processes that MVB are involved with.…”
Section: Discussionsupporting
confidence: 54%
“…MVBs might also be involved in recycling membranes. Although the presence of MVBs and their roles as prevacuolar compartments for lytic and storage vacuoles, in vacuolar receptor recycling, and in internalization and secretion of arabinogalactan-rich glycoproteins have been described [2,4,5,[13][14][15][16]18], only a few reports have identified components of the ESCRT-machinery in plants [53,54,67]. Here we show by cross-species comparisons that most protein entry components and all the ESCRT-components are present in Arabidopsis and rice.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…He described a close association of a tubular ER network with the nascent cell plate, surrounding the latter structure. Recent electron tomographic analysis of cell plate formation in meristematic cells of Arabidopsis prepared by high-pressure freezing showed that few ER membranes associated with the cell plate during the initial stages of the cell plate formation, but that this increased towards cell plate completion (Seguí-Simarro et al 2004). However, there is no direct evidence that ER contributes to the membranous structures involved in cell plate formation.…”
Section: Does the Endoplasmic Reticulum Contribute To The Cell Partitmentioning
confidence: 99%
“…Electron tomography, which is a powerful electron microscopic technique for getting a nano-scale three-dimensional analysis, has been used in the ultrastructural studies of cytokinesis of land plants (Otegui and Staehelin 2004, Segui-Simarro et al 2004, Haas and Otegui 2007. This technique will be also useful for analysis of tiny PD structure, in order to investigate their ultrastructure and the process of their formation.…”
Section: Introductionmentioning
confidence: 99%